2003
DOI: 10.1016/s1567-1356(02)00203-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression analyses: Metabolic adaptation of to high sugar stress

Abstract: The transcriptional response of laboratory strains of Saccharomyces cerevisiae to salt or sorbitol stress has been well studied. These studies have yielded valuable data on how the yeast adapts to these stress conditions. However, S. cerevisiae is a saccharophilic fungus and in its natural environment this yeast encounters high concentrations of sugars. For the production of dessert wines, the sugar concentration may be as high as 50% (w/v). The metabolic pathways in S. cerevisiae under these fermentation cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(146 citation statements)
references
References 70 publications
8
128
1
5
Order By: Relevance
“…As shown in Table 2, the EC1118 commercial strain performed worse than the two wine isolated strains, since a high level of residual sugar, associated with lower ethanol production, was detected at the end of the monitoring period. A notable production of acetic acid was concomitantly observed, most likely due to the osmotic stress provoked by the high concentration of sugars, responsible for the upregulation of the genes encoding for aldehyde dehydrogenases (12). It should be underlined that differences in the vitality counts were observed for the three S. cerevisiae strains when inoculated as pure culture in the must utilized here.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As shown in Table 2, the EC1118 commercial strain performed worse than the two wine isolated strains, since a high level of residual sugar, associated with lower ethanol production, was detected at the end of the monitoring period. A notable production of acetic acid was concomitantly observed, most likely due to the osmotic stress provoked by the high concentration of sugars, responsible for the upregulation of the genes encoding for aldehyde dehydrogenases (12). It should be underlined that differences in the vitality counts were observed for the three S. cerevisiae strains when inoculated as pure culture in the must utilized here.…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that the response of S. cerevisiae to osmotic stress can result in increased acetic acid contents due to the upregulation of genes encoding for aldehyde dehydrogenases. In fact, yeast grown in 40% (wt/vol) sugar juice produced 1.35 g of acetic acid/liter compared to 0.3 g/liter at the lower sugar concentration (22% [wt/ vol]) (12). The acetic taste in these wines is in part masked by the high residual sugars after fermentation.…”
mentioning
confidence: 99%
“…Technology is now available to determine the genome-wide transcriptional response of yeast to environmental changes and has been used to elucidate the transcriptional response to a number of brewery-relevant parameters, including, for example, availability of oxygen and anaerobiosis (Aguilera et al, 2005;Lai et al, 2005), ageing (Fabrizio et al, 2005;Laun et al, 2005), dehydration and hydration (Singh et al, 2005), ethanol toxicity (Alexandre et al, 2001;Caba et al, 2005;Fujita et al, 2006;van Voorst et al, 2006), glucose repression and diauxic shift (DeRisi et al, 1997;Griffin et al, 2002), nutrient limitation (Causton et al, 2001;Gasch et al, 2000), osmotic stress (Gasch et al, 2000), oxidative stress (Causton et al, 2001;Gasch et al, 2000;Koerkamp et al, 2002), pH (Causton et al, 2001), salt stress (Caba et al, 2005), sugar stress (Ando et al, 2006;Erasmus et al, 2003) and temperature change (Causton et al, 2001;Gasch et al, 2000;Homma et al, 2003;Sahara et al, 2002). However, very few studies have utilized production strains of yeast or have involved incubation in brewery wort (Smart, 2007).…”
Section: B R Gibson Et Almentioning
confidence: 99%
“…Several transcriptomic studies have also been published for research conducted with wine yeast strains (Erasmus et al, 2003;Rossignol et al, 2003;Varela et al, 2005;Mendes-Ferreira et al, 2007;Marks et al, 2008;Pizarro et al, 2008;Rossouw & Bauer, 2008). These studies have illuminated the intrinsic genetic and regulatory mechanisms involved in fermentation, and have greatly increased our understanding of this important process.…”
Section: -Transcriptomicsmentioning
confidence: 99%